Natural killer-like nonspecific tumor cell lysis mediated by specific ligand-activated Vα14 NKT cells - Kawano, Tetsu (The National Academy of Sciences, 1998)
We have recently identified α-galactosylceramide (α-GalCer) as a specific ligand for an invariant Vα14/Vβ8.2 T cell receptor exclusively expressed on the majority of Vα14 NKT cells, a novel subset of lymphocytes. Here, we report that α-GalCer selectively activates Vα14 NKT cells resulting in prevention of tumor metastasis. The effector mechanisms of the ligand-activated Vα14 NKT cells seem to be mediated by natural killer (NK)-like nonspecific cytotoxicity. Indeed, the cytotoxic index obtained by α-GalCer-activated Vα14 NKT cells was reduced by the addition of cold target tumor cells or by treatment with concanamycin A, which inhibits activation and secretion of perforin, but not by mAbs against molecules involved in the NKT cell recognition and conventional cytotoxicity, such as CD1d, Vβ8, NK1.1, Ly49C, Fas, or Fas ligand. These results suggest that the ligand-activated Vα14 NKT cells kill tumor cells directly through a CD1d/Vα14 T cell receptor-independent, NK-like mechanism.